2016
DOI: 10.3390/met6030052
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Post Weld Heat Treatment on Strength of Three Aluminum Alloys Used in Light Poles

Abstract: Abstract:The conjoint influence of welding and artificial aging on mechanical properties were investigated for extrusions of aluminum alloy 6063, 6061, and 6005A. Uniaxial tensile tests were conducted on the aluminum alloys 6063-T4, 6061-T4, and 6005A-T1 in both the as-received (AR) and as-welded (AW) conditions. Tensile tests were also conducted on the AR and AW alloys, subsequent to artificial aging. The welding process used was gas metal arc (GMAW) with spray transfer using 120-220 A of current at 22 V. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 8 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…Likewise, Elangovan and Balasubramanian 39 showed that the appropriate PWHT in AA6061 welded joints increased the joint efficiency from 66% for the AW condition to approximately 77%. Menzemer et al 40 also reported the increase of the yield stress and of the ultimate tensile strength in welded joints from three differen aluminum alloys from 6xxx alloying series with the appropriate artificial aging conditions.…”
Section: Results and Disussionmentioning
confidence: 97%
“…Likewise, Elangovan and Balasubramanian 39 showed that the appropriate PWHT in AA6061 welded joints increased the joint efficiency from 66% for the AW condition to approximately 77%. Menzemer et al 40 also reported the increase of the yield stress and of the ultimate tensile strength in welded joints from three differen aluminum alloys from 6xxx alloying series with the appropriate artificial aging conditions.…”
Section: Results and Disussionmentioning
confidence: 97%
“…As can be seen in Figure 5b, the crack seems to be propagated at the boundary between these two patterns. In the literature, these features are often associated to a forged weld between two pieces characterized by dissimilar compositions (L' Hèritier et al 2013, Menzemer et al 2016.…”
Section: Microstructurementioning
confidence: 99%
“…Different post-weld heat treatment (PWHT) techniques are usually applied to improve the mechanical performances of welded joints of heat-treatable aluminum alloys. A number of research studies have investigated the application of PWHT to different aluminum alloy welded joints using various welding processes [15][16][17][18]. Balasubramanian et al [19] researched the effect of pulsed current and PWHT on the tensile properties of TIG welded and metal inert gas (MIG) welded high-strength aluminum alloys; they noted that more precipitates were formed after a soaking period of 24 h at 125 • C, and their uniform distribution led to a higher strength and hardness.…”
Section: Introductionmentioning
confidence: 99%